Reformulation of Public Participation in Fast- Track Legislation in an Open Cumulative National Legislative Program: Reformulasi Partisipasi Publik dalam Pembentukan Undang-Undang secara Cepat pada Prolegnas Kumulatif Terbuka - Perdana, Anugerah; Enggal, Carolus Boromeus; Mahdum, Raden; Listiawati, Erna (Constitutional Court of the Republic of Indonesia, Indonesia, 2023)
One of the factors contributing to the suboptimal implementation of “meaningful participation” is the exploitation of legal loopholes to expedite the creation of open cumulative draft laws (RUU). This issue is further complicated by Constitutional Court Decision Number 90/PUU XVIII/2020, which states that the formation of open cumulative draft laws does not necessitate general public participation, thereby posing a distinct challenge. In the context of this matter, by employing a normative legal research method, the author examines the urgency of public participation in the development of open cumulative draft laws through a “fast track” legislative process. The study’s results cover three main topics: (1) the mechanism of open cumulative draft law design and its relationship to “fast track” legislation; (2) the legal implications stemming from the Constitutional Court’s considerations regarding public participation in the creation of open cumulative draft laws; (3) the essence of integrating public participation into open cumulative draft laws using the “fast track” legislative method.